Ultralight lithography [IC manufacture]. - Harned, N. (IEEE spectrum)
Smaller IC features-in particular, narrower connecting linewidths-require the development of more precise tools. One key technology is semiconductor lithography, essentially the photographic transfer of IC features onto silicon substrates. As the wavelength of the light source used to expose IC patterns on wafers decreases, the properties of the camera system used for creating these minuscule patterns have become more crucial. One potential next-generation lithographic technology is extreme ultraviolet (UV), which promises to produce IC-feature sizes as small as 30 nm using a reflective camera system and a wavelength of 13.4-nm. The author discusses the reasons for using extreme UV lithography and describes the illumination system, optical materials and coatings, resolution and depth of focus issues, reticles and masks and chemically amplified photoresists